ANALISIS AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (ADD) DI DESA SUKAMAJU KECAMATAN TOBELO BARAT KABUPATEN HALMAHERA UTARA - Frangsisko Manggiwo, Ardi; Hi. Posi, Sahrul; Manoma, Suharli (CV. Anugerah Duta Perdana, 2023)
This study was conducted to analyze the accountability of the management of Village Fund Allocation in Sukamaju Village, North Tobelo District, North Halmahera Regency. This study aims to determine the Planning, Implementation, and Accountability of Village Fund Allocation. The type of research used is descriptive qualitative, namely research conducted in accordance with the situation and conditions required by using existing data sources. The results of this study indicate that the planning and implementation accountability system has implemented the principles of transparency and accountability. While the Village Fund Allocation Accountability (ADD) both technically and administratively is good, but it must still receive or be given guidance from the government considering the system is always changing.